Semi-professional rugby union players may be at risk of low-energy availability - Roberts, C.; Beaven, C.; Posthumus, L.; Gill, N.; Sims, S. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Rugby players should aim to consume enough food to meet energy, macronutrient and micronutrient requirements. Failure to do so can negatively impact performance, recovery, health, well-being, cognitive function and may increase injury risk. Provincial academy players in New Zealand typically present congested schedules; alongside developmental rugby athletes will train and play at the local club level and balance study and work commitments. As such, monitoring and management of dietary intake is crucial.